Mineral Composition (Ca, Mg, K, and Na) in the Culture Water of Pacific White Shrimp (Litopenaeus vannamei) in Purworejo Village, Pasir Sakti District, East Lampung - Wuni Alfionita; Ellen Larasati; Asmaul Husna (Fakultas Pertanian Universitas Samudra, 2026)
Minerals are essential components of shrimp culture water, playing important roles in osmoregulation, growth, and survival of Pacific white shrimp (Litopenaeus vannamei). This study aimed to analyze the mineral content of water used for L. vannamei culture in Purworejo Village, Pasir Sakti District, East Lampung Regency, Indonesia. The observed mineral parameters included calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na). Water samples were collected from three shrimp ponds at 5, 20, and 35 days of culture (DOC) and analyzed using a descriptive approach. The results showed that Ca concentrations ranged from 186.7 to 266.7 mg/L, Mg from 307.4 to 396.4 mg/L, K from 43.3 to 70.8 mg/L, and Na from 1,767.5 to 4,308.6 mg/L. Compared with the recommended ranges for optimal L. vannamei culture, most mineral concentrations were relatively low. These conditions may affect water quality and potentially limit shrimp growth performance. Therefore, mineral supplementation and appropriate water quality management are recommended to improve culture conditions and support sustainable shrimp production.